Design and evaluation of the Afari: A three-wheeled mobility and balance support device for outdoor exercise. - Alizadeh Noghani, Mohsen; Browning, Drew; Caccese, Vincent; DePoy, Elizabeth; Gilson, Stephen; Beaumont, Ryan; Hejrati, Babak (Assistive Technology, 2024)
This article presents the engineering design and preliminary testing of the AfariTM mobility device and the integrated IntracTM activity tracking system. The patented Afari design is a three-wheeled device that assists users of any age with mobility impairments with outdoor exercise and movement in various environments and surfaces. We devised methods for testing of the Afari to ensure safe and flexible mobility assistance and demonstrated a high level of stability and structural integrity suitable for vigorous outdoor exercise. A smartphone-based sensing system, the Intrac, was designed for and integrated with the Afari to monitor the user's interaction forces and important gait parameters. The Intrac offers a graphical user interface for displaying and sharing measurements with users and providers, and the accuracy of its measurements was validated by testing its individual components. A preliminary subject study showed that the participants could use the Afari for various levels of weight compensation during walking, while the Intrac enabled the measurement of interactive forces on their arms and key gait parameters. The results demonstrate the potential of the Afari and Intrac to provide a safe walking experience in a variety of terrains and continuously monitor users' gait.